Social Ecology and The Growth Machine Coalition in The Surabaya Policy Dilemma - Siti Aminah; A. Hesti Susanti; Roikan Soekartun (Departement of Architecture, Universitas Islam Indonesia, 2018)
This study integrates theoretical and analytical approaches of social ecology, urban growth machine, and urban governments. The aim is to explain forms of contrast collaboration between government (political elite) and private developers (local businesses). Political elite rests on the ideological commitment to collaborate within local individual authorities who see the growth of a city led by the market. City governments work in relatively independent and informal networks that rely on local government bureaucratic structures. The practice of government and private coalition faces social ecology challenges. The development of a city not only creates new economic growth area (within the corridors of independent city’s development) but also generates centers of the social ecology crisis. This study uses qualitative methods and takes the form of case studies. Research results show that the operation of the urban growth machine run by the Surabaya government and the private economic power (developers) have not merely carried out sustainable development, produced various advancements for the city and its population but caused losses to the group that let go of their soil (land) to the developer. The power of the city government is a systemic power that shapes the process of coalition building within the dilemmatic process of making regulations and public policies.Keywords: Urban growth machine, developer, city governments, the policy dilemma